Aquatic Macrofauna Assessment Along Agno River in the Province of Pangasinan, Philippines - Dantis, Marjorie; Lacap, Marjorie (Southeast Asian Journal of Science and Technology, 2021)
The study assessed the aquatic macrofauna diversity along Agno River in Pangasinan. It classified biodiversity in terms of macrofauna diversity, dominance, richness, and evenness. There were 32 macrofauna species found which included 23 fishes, five crustaceans, and four mollusks. In terms of the month of sampling, results revealed no significant differences in macrofauna diversity, dominance, richness, and evenness. The macrofauna species were assessed to be very low (H’=1.60). However, there were significant differences in macrofauna diversity, richness, dominance, and evenness among the five sampling stations. The dominant species found along Agno River was Oreochromis niloticus.